Effective reduction of primary dysmenorrheal symptoms through concurrent use of n-3 fatty acids and Rosa damascena extract (RDE) - Davaneghi S; Tarighat-Esfanjani; Safaiyan A; Fardiazar Z (Zanjan University of Medical Sciences and Health Services, 2017)
Background: Primary dysmenorrhea (PD) is characterized by painful cramps of lower abdomen without abnormal pelvic pathology. PD begins some hours before or simultaneously with the onset of menstrual bleeding. Objectives: The purpose of this study was to investigate the effects of separate and concurrent supplementation of fish oils (FO) containing n-3 fatty acids and Rosa Damascena extract (RDE) on PD symptoms. Methods: In this double blind clinical trial in 2015, through convenience sampling, 105 university students with primary menstrual pain in most recent years, without abnormal pathology, and with moderate/severe dysmenorrheal symptoms according to visual analogue scale (VAS) were randomly assigned into one of four groups: 1. FO 1000 mg/day (n=26), 2. RDE 1000 mg/day (n=27), 3. FO and RDE concurrently, with the same dose (n=27), and 4. Control group (n=25). All measurements were performed three times, at the beginning, 30th day, and 60th day. Symptoms including nausea, vomiting, diarrhea, bloating, cramp, low back pain, headache, fatigue, anxiety, sweat, weakness, dizziness, drowsiness, and feeling cold were measured by VAS. Results: After 2-month treatment, supplementation with RDE significantly reduced severity of bloating (p<0.001) and sweat (p<0.001), but FO supplementation had no significant effect on PD symptoms. The concurrent use of FO and RDE significantly decreased severity of diarrhea (p=0.038), weakness (p<0.001), dizziness (p=0.003), and feeling cold (p=0.049). Conclusion: Our results suggest that the concurrent supplementation of omega-3 fatty acids and RDE could be more effective than their separate use in decreasing PD symptoms; however, larger trials are warranted to confirm these preliminary findings.